Excel spreadsheet applications series for accounting principles - Smith, Gaylord N. (Cincinnati, Ohio : South-Western College, 1999)
This book contains typical homework problems which have been restructured so that they can be solved using a spreadsheet program called Excel for Windows.
Keywords: Accounting; Microsoft Excel; Microsoft Excel for Windows; Accounting -- Data processing; Electronic spreadsheets